Changes in Motor, Cognitive, and Behavioral Symptoms in Parkinson's Disease and Mild Cognitive Impairment During the COVID-19 Lockdown - Baschi, Roberta; Luca, Antonina; Nicoletti, Alessandra; Caccamo, Maria; Cicero, Calogero Edoardo; D'Agate, Concetta; Di Giorgi, Lucia; La Bianca, Giuseppe; Lo Castro, Tiziana; Zappia, Mario; Monastero, Roberto (Frontiers in Psychiatry, 2020)
Objective: The effect of COVID-19 lockdown on subjects with prodromal phases of dementia is unknown. Aim of the study was to evaluate the motor, cognitive and behavioural changes during Italian COVID-19 lockdown in patients with Parkinson’s disease with and without Mild Cognitive Impairment (PD-MCI and PD-NC) and in patients with MCI not associated with PD (MCI). Methods: 34 patients with PD-NC, 31 PD-MCI and 31 MCI and their caregivers were interviewed 10 weeks after COVID-19 Italian lockdown, examining changes in cognitive, behavioural and motor symptoms. Furthermore, standardized scales including the Neuropsychiatric Inventory (NPI) and the Movement Disorder Society, Unified Parkinson's Disease Rating Scale (MDS-UPDRS) part I and II were administered. Multivariate logistic regression was carried out to evaluate associated covariates comparing PD-NC versus PD-MCI and MCI versus PD-MCI. Results: All groups showed worsening of cognitive (39.6%),pre-existing (37.5%) and new (26%) behavioural symptoms, and motor symptoms (35.4%) during COVID-19 lockdown, resulting in increased caregiver burden in 26% of cases. After multivariate analysis PD-MCI was significantly and positively associated with IADL lost during quarantine (OR 3.9, CI 1-61-9.58), when compared to PD-NC. In the analysis of MCI versus PD-MCI, the latter showed a statistically significant worsening of motor symptoms than MCI (OR 7.4, CI 1.09-45.44). Regarding NPI items, nightime behaviors statistically differed in MCI versus PD-MCI (16.1% versus 48.4%, p=0.007). MDS-UPDRS part I and II revealed that PD-MCI showed significant higher frequency of cognitive impairment (p=0.034), fatigue (p=0.036) and speech (p=0.013) than PD-NC; differently, PD-MCI showed significant higher frequencies in several MDS-UPDRS items than MCI, particularly: pain (p=0.001), turning in bed (p=0.006), getting out of bed (p=0.001) and walking and balance (p=0.003). Conclusion: COVID-19 quarantine is associated with the worsening of cognitive, behavioural and motor symptoms in subjects with MCI of neurodegenerative aetiology, particularly in PD-MCI. There is a need to implement specific strategies in order to contain the effects of quarantine in patient with PD and cognitive impairment and their caregivers.